Modifikasi dan Karakterisasi Titania (M-TiO2) Dengan Doping Ion Logam Transisi Feni dan Cuni - Rilda, Yetria; Arief, Syukri; Dharma, Abdi; Alif, Admin (Jurnal Natur Indonesia, 2010)
Structure and size of titania nanoparticles have been modified with doping the transition metal (FeNiand CuNi) and controlling the calcinations temperature. Gel and M-TiO 2 powder were characterized byFT-IR showed the changed in intensity at 4000-400 cm-1. TG-DTA curve show the weigh of sample wasdecreased with the increasing of temperature 25-800°C. XRD pattern used to identify the titania structureshows the highest intensity of anatase at temperature calcination as 500°C. XRD of FeNi-TiO 2 and CuNi-TiO2 FeNi 10.5-41.9 nm and CuNi 12.1-33.5 converted using Debye-Scherrer’s equation and TEM analysisthe distribution of crystal size as FeNi-TiO2 and CuNi-TiO2 10-15 nm. SEM has shown that morphology ofdifferent surface from the FeNi-TiO 2 and CuNi-TiO 2 at different calcinations temperatures. Titaniacomposition can be determined by EDX analysis give as FeNi-TiO2 1:1, 97.01% and CuNi-TiO2 1:1, 94.63%respectly. The surface area has been determined by BET as FeNi-TiO 2 was 64.38 m2/g and CuNi-TiO2was 40.9 m2/g.